2022
DOI: 10.1007/s00424-022-02686-8
|View full text |Cite
|
Sign up to set email alerts
|

Single nephron glomerular filtration rate measured by linescan multiphoton microscopy compared to conventional micropuncture

Abstract: Renal micropuncture, which requires the direct access to the renal tubules, has for long time been the technique of choice to measure the single nephron glomerular filtration rate (SNGFR) in animal models. This approach is challenging by virtue of complex animal preparation and numerous technically difficult steps. The introduction of intravital multiphoton microscopy (MPM) offers another approach to the measure of the SNGFR by mean of the high laser-tissue penetration and the optical sectioning capacity. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In particular, fluorescence microscopy is a milestone in the field of microscopy. This has been instrumental in elucidating cellular pathophysiology both in vitro [ 15 , 16 , 17 ] and in vivo [ 18 , 19 , 20 ], as well as in testing the efficacy of pharmacological compounds for researching genetic disorders [ 21 , 22 ]. Fluorescence microscopy was used to show images of the organs of a 14-month-old child who died from SARS-CoV-2 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fluorescence microscopy is a milestone in the field of microscopy. This has been instrumental in elucidating cellular pathophysiology both in vitro [ 15 , 16 , 17 ] and in vivo [ 18 , 19 , 20 ], as well as in testing the efficacy of pharmacological compounds for researching genetic disorders [ 21 , 22 ]. Fluorescence microscopy was used to show images of the organs of a 14-month-old child who died from SARS-CoV-2 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in animals with AKI indicate that the sustained reduction in renal blood flow and GFR is a consequence of overactivation of the tubuloglomerular feedback, secondary to proximal tubular necrosis [28]. It would be interesting in future studies to evaluate the tubuloglomerular feedback, the SNGFR, and the morphology of the proximal tubular epithelium in these groups of animals, especially since SNGFR and the morphology can now be evaluated by linescan multiphoton microscopy [29]. Interestingly, we confirmed that the expression of SerpinA3K increased after AKI, specifically in tubular cells, where it was relocated to the apical membrane [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, old protocols for in vivo and in vitro experiments have been progressively optimized or substituted by new ones. In other cases, a synergic combination of more approaches has been useful to elucidate many biological processes [ 91 , 92 , 93 , 94 , 95 ]. The great advancement in the fields of genomics, bioinformatics, structural biology, and immunology offered new tools to improve the efficacy of new vaccine formulations against the AMR.…”
Section: Next Generation Vaccinesmentioning
confidence: 99%